2022
DOI: 10.1155/2022/8317011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Treatment with Colchicine after Acute Coronary Syndrome on Major Cardiovascular Events: A Systematic Review and Meta-Analysis of Clinical Trials

Abstract: Aim. Colchicine as an anti-inflammatory drug might be effective in the treatment of atherosclerosis, an inflammatory-based condition. The aim of this systematic review and meta-analysis was to evaluate the impact of colchicine on acute coronary syndrome (ACS). Methods. We searched SCOPUS, PubMed, and Web of Science up to September 27, 2020. All clinical trials which evaluated the effect of colchicine on ACS patients and reported high-sensitivity C-reactive protein (hs-CRP) serum level or gastrointestinal (GI) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Although the detailed mechanism of AAA pathogenesis is still unclear, the involvement of inflammation in the formation and progression of AAAs has become a consensus in this field (38). CRP, as one of the important inflammatory acute phase proteins, is involved in the development of many cardiovascular diseases (39)(40)(41)(42)(43)(44)(45). In this study, we found increased expression of CRP protein in experimental AAAs.…”
Section: Discussionmentioning
confidence: 69%
“…Although the detailed mechanism of AAA pathogenesis is still unclear, the involvement of inflammation in the formation and progression of AAAs has become a consensus in this field (38). CRP, as one of the important inflammatory acute phase proteins, is involved in the development of many cardiovascular diseases (39)(40)(41)(42)(43)(44)(45). In this study, we found increased expression of CRP protein in experimental AAAs.…”
Section: Discussionmentioning
confidence: 69%
“…Notably, colchicine has a narrow therapeutic window, and actually, adverse effects related to the administration of colchicine have been extensively evaluated. 62 A previous meta-analysis has also revealed a significant association between the administration of colchicine and AEs and suggested that higher dose was harder to be intolerable. 63 Undoubtedly, the adverse effects caused by higher dose will compromise its therapeutic benefits, therefore leading to the result that higher dose is inferior to lower dose in the therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%